Lignocellulosic nanofibers from triticale straw: the influence of hemicelluloses and lignin in their production and properties - Tarrés, Quim (2017)
The present work aims to determine the influence of hemicellulose and lignin content in the production of lignocellulosic nanofibers (LCNF) from triticale straws. Triticale straws were digested and then gradually delignified, preserving as much hemicelluloses as possible. The obtained LCNF were characterized and used as paper strength additive, observing that hemicellulose and lignin have a key role on the final properties thereof, as well as on their reinforcing potential as paper additive, obtaining LCNF with the same paper reinforcing potential than CNF obtained by TEMPO ((2,2,6,6-Tetramethyl-piperidin-1-yl)oxyl) mediated oxidation.